Comparison of Phenylephrine Infusion Versus Boluses for Management of Blood Pressure in Elective Caesarean Section - Muhammad Mohsin Riaz; Syed Qasim Ali Shah; Muhammad Saad Sikander; Waqas Tariq (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the efficacy of intravenous phenylephrine infusion versus boluses for blood pressure management in elective caesarean sections.